Color-Dressed Generalized Biadjoint Scalar Amplitudes: Local Planarity - Cachazo, Freddy; Early, Nick; Zhang, Yong (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
The biadjoint scalar theory has cubic interactions and fields transforming in the biadjoint representation of SU() × SU(Ñ). Amplitudes are ''color'' decomposed in terms of partial amplitudes computed using Feynman diagrams, which are simultaneously planar with respect to two orderings. In 2019, a generalization of biadjoint scalar amplitudes based on generalized Feynman diagrams (GFDs) was introduced. GFDs are collections of Feynman diagrams derived by incorporating an additional constraint of ''local planarity'' into the construction of the arrangements of metric trees in combinatorics. In this work, we propose a natural generalization of color orderings that leads to color-dressed amplitudes. A generalized color ordering (GCO) is defined as a collection of standard color orderings that is induced, in a precise sense, from an arrangement of projective lines on ℝℙ². We present results for ≤ 9 generalized color orderings and GFDs, uncovering new phenomena in each case. We discover generalized decoupling identities and propose a definition of the ''colorless'' generalized scalar amplitude. We also propose a notion of GCOs for arbitrary ℝℙᵏ⁻¹, discuss some of their properties, and comment on their GFDs. In a companion paper, we explore the definition of partial amplitudes using CEGM integral formulas.